STEMbach Experiences at Higher Education - Castro-Santos Laura; Guillén Félix Puime; Lamas-Galdo Isabel; García-Diez Ana Isabel; Díaz Joaquín Enríquez; Boedo-Vilabella Lucía; Lagoa-Varela María Dolores; Álvarez-García Begoña; Filgueira-Vizoso Almudena (De Gruyter, 2023)
The aim of this work is to describe several experiences of STEMbach in different areas: engineering, economics, materials, etc. The STEMbach is a program carried out by high school students during their two years of study to obtain their High School Diploma (equivalent to A-levels), designed for both the Humanities and Sciences modalities, and created alongside the Galician strategy for digital education. It encourages the vocation of the scholars towards scientific and technological research and allows a connection directly with the college education. The STEM works explained in this work were developed between the University of A Coruña and several high schools located in the region of Galicia (North-West of Spain). Results were very constructive for promoting STEM careers.